A six-stage framework for evolutionary IS research using path models: Conceptual development and a social networking illustration. Issue 1 (14th March 2016) - Kock, Ned; Moqbel, Murad
Abstract : Purpose: – The purpose of this study is to fill a gap in evolutionary theorizing in the field of information systems. Evolutionary theorizing has recently been added as a useful tool to the research repertoire of information systems investigators. However, the literature on evolutionary theorizing and related empirical research lacks a clear framework that explicitly shows how information systems researchers can go, step-by-step, from a generic model of the evolution of traits in our ancestral past to a more specific model depicting the effects of technology facilitation of those traits among modern humans. The purpose of this study is to fill this gap through a framework composed of six stages. Design/methodology/approach: – To discuss and illustrate the framework, the authors develop an easy-to-understand generic path model explicitly depicting relationships among variables related to events that occurred in our evolutionary past. We then incrementally adapt this generic path model, eventually arriving at a focused path model depicting causal relationships among social networking site use, job satisfaction, organizational commitment and job performance. In doing so, the authors also develop a theoretical model about how social networking site use can affect job performance, where a positive total effect is predicted via positive intermediate effects on job satisfaction and organizational commitment. Findings: – To discuss the final stage in the framework, the authors present an illustrative example where the focused path model is tested based on a study of the effect of Facebook use on job performance among 178 working professionals across the USA. This illustrative example provides general support for the theoretical model. Research limitations/implications: – The counterintuitive hypothesis that Facebook use is associated with increased job performance is supported. Practical implications: – Social networking site use by organizational employees is likely to be associated with improved job performance. Originality/value: – This study provides a clear framework that shows how researchers can go from a generic evolutionary path model in our ancestral past to a more specific model comprising technology effects in modern humans.